CBIO-07. CELL DEATH INDUCED BY AN OSCILLATING MAGNETIC FIELD IN PATIENT DERIVED GLIOBLASTOMA CELLS IS MEDIATED BY REACTIVE OXYGEN SPECIES - Hambarde, Shashank (Neuro Oncol, 2020)
Noninvasive cancer therapy with minimal side effects would be ideal for improving patient outcome in the clinic. We have developed a novel therapy using strong rotating magnets mounted on a helmet. They generate oscillating magnetic fields (OMF) that penetrate through the skull and cover the entire brain. We have demonstrated that OMF can effectively kill patient derived glioblastoma (GBM) cells in cell culture without having cytotoxic effects on cortical neurons and normal human astrocytes (NHA). Exposure of GBM cells to OMF reduced the cell viability by 33% in comparison to sham-treated cells (p< 0.001), while not affecting NHA cell viability. Time lapse video-microscopy for 16 h after OMF exposure showed a marked elevation of mitochondrial reactive oxygen species (ROS), and rapid apoptosis of GBM cells due to activation of caspase 3. Addition of a potent antioxidant vitamin E analog Trolox effectively blocked OMF-induced GBM cell death. Furthermore, OMF significantly potentiated the cytotoxic effect of the pro-oxidant Benzylamine. The results of our studies demonstrate that OMF-induced cell death is mediated by ROS generation. These results demonstrate a potent oncolytic effect on GBM cells that is novel and unrelated to any previously described therapy, including a very different mechanism of action and different technology compared to Optune therapy. The effect is very powerful, and unlike Optune, can be seen within hours after initiation of treatment. We believe that this technology holds great promise for new, effective and nontoxic treatment of glioblastoma.